Islamic Manuscripts of Meranaw Muslims In Mindanao: An Inquiry of The Richness of The Intellectual Heritage - Labi Hadji Sarip Riwarung (Al-Albab, 2021)
This inquiry on the Islamic manuscripts intends to illuminate the rich artistic and intellectual writing traditions of the Meranaw Muslims in the Philippines. These Meranaw manuscripts play an important role in guiding people’s lives as a source of religious knowledge that reflects people’s thoughts and aspirations. Moreover, these manuscripts are additionally an important source of knowledge in understanding people’s culture, history, and relationships with other nations, such as Malaysia, Indonesia, Saudi Arabia, Brunei, and more. These manuscripts are handwritten in Arabic script called batang a Arab or in Jawi or kirim. Some of these manuscripts are the handwritten Qur’an, kisas (Islamic stories), prayer scrolls, medicinal manuscripts or mga bolongs, book of kakasi (book of charms), and the ilmo extreme unction and other Islamic manuscripts of importance to the Meranaw. There are also Islamic manuscripts that are written in stencil and printed like the Parokonan, the introductory guide to prayer, Alipalipan ( a book for beginners of the Arabic alphabet), Mawlid/ Barsindi (the devotional song about Prophet Muhammad (P.U.H)), Taabir Mimpi (the book of prophecy), qira’a, Sarf, and Tajwid. To the Meranaws, manuscripts are family belongings with great personal value. They are a family treasure handed down from generation to generation and strictly guarded with great care. Families cover the manuscripts with cloth or skin of an animal for protection and lock them in a chest so that they will be accessed only by their family. This research paper presents the Islamic Manuscript of the Meranaw, describes its characteristics and contents to explain the tremendous value to the Meranaw Society, hence the richness of the archival libraries mentioned.